MODEL EXPERIENTIAL LEARNING TERHADAP PERILAKU STRANGER SAFETY PADA SISWA AUTIS DI SMP - WASKITHO, NUGROHO (Jurnal Pendidikan Khusus, 2018)
ABSTRACT An experiential learning was a learning which took the students part in direct experience. A stranger safety behavior was someone’s attitude in facing those who were not known yet in order that they could interact and communicate well, could understand how someone would do crime and what thing should be done to avoid someone’s crime intention. In this case, someone with autism disturbance should also have good stranger safety in the view of limitedness and disturbance belonged. So, the focus of this research specifically observed about how the application, problem, and effort were to handle the problems related with the application of experiential learning model toward stranger safety behavior to autism students. This research used experiment research with single subject arrangement with A-B-A design. This research subject was one autism student in SMP Negeri 2 Sedati Sidoarjo. Based on the analysis done it was indicated that in baseline phase (A1) the subject had stranger safety behavior with percentage score 33% with the stability extent (0,6) and mean level (3,66) and it was obtained upper limit i.e. (3,96) and below limit i.e. (3,36). In intervention phase (B) stranger safety behavior got percentage 80% so it indicated stable data with stability extent (1,2) and mean level (6,4) and it was obtained upper limit (7) and below limit (5,8). And, in baseline phase (A2) the subject’s score of stranger safety behavior reached 100% so it indicated stable data with stability extent (0,6) and mean level (7,66) and it was obtained upper limit (7,96) and below limit (7,36). According to the data analysis and discussion it could be concluded that the experiential learning model could experience to enhance the stranger safety behavior which it obtained the highest score 4 in baseline phase (A1) before and after intervention in baseline phase (A2) it obtained the highest score 8.   Keywords: Experiential learning model, stranger safety behavior